2021
DOI: 10.1051/matecconf/202134304007
|View full text |Cite
|
Sign up to set email alerts
|

Common defects of parts manufactured through single point incremental forming

Abstract: Single point incremental forming is one of the most intensely researched die-less manufacturing process. This process implies the usage of a CNC equipment or a serial robot which deforms a sheet metal with the help of a relatively simple tool that follows an imposed toolpath. As every cold metal forming process, besides the many given advantages it has also some drawbacks. One big drawback in comparison with other cold metal forming processes is the low accuracy of the deformed parts. The aim of this research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…The computational results showed that moth-flame optimisation, multiverse optimisation and Harris Hawk optimisation provided highly competitive geometry optimisation results. Popp et al (2021) investigated the sheet bending mechanism in the ISF of Al-Cu4PbMgMn aluminium alloy blanks using finite element based analysis. The study showed that the shape of the retaining rings significantly influenced the final geometric accuracy of the parts produced by ISF.…”
Section: Introductionmentioning
confidence: 99%
“…The computational results showed that moth-flame optimisation, multiverse optimisation and Harris Hawk optimisation provided highly competitive geometry optimisation results. Popp et al (2021) investigated the sheet bending mechanism in the ISF of Al-Cu4PbMgMn aluminium alloy blanks using finite element based analysis. The study showed that the shape of the retaining rings significantly influenced the final geometric accuracy of the parts produced by ISF.…”
Section: Introductionmentioning
confidence: 99%
“…The computational results prove that moth-flame optimization, multiverse optimization and Harris Hawk optimization are very competitive in geometry optimization. Popp et al [30] studied the sheet metal bending mechanism in the SPIF of AlCu4PBMgMN aluminium alloy drawpieces using an FE-based method analysis. It was found that the shape of the retaining rings has a large influence on the final geometrical accuracy of the parts manufactured using SPIF.…”
Section: Introductionmentioning
confidence: 99%